Survey of Body Mass Index and VO2 Max in Futsal Extracurricular Students - Al Hafidz, Muhamad Syauqi; Yunus, Moch.; Widiawati, Prisca (Physical Activity Journal (PAJU), 2024)
This study aims to determine the body mass index and VO2 Max endurance of futsal extracurricular students of State Junior High School 68 Jakarta. This research is a quantitative descriptive study with the futsal extracurricular students of State Junior High School 68 Jakarta as research subjects, totaling 20 people. The research sample was taken using the total sampling method. The data collection process was taken using measurement and test instruments: 1). Measurement of body weight and height (body mass index) 2). VO2 Max (bleep test). Overall, this study resulted in the average body mass index measurements of futsal extracurricular students of State Junior High School 68 Jakarta being 17.7, which was included in the thin category (Underweight). The average value of the VO2 Max endurance test of futsal extracurricular students of State Junior High School 68 Jakarta was 38.6, included in the Intermediate category. The findings can inform educators and policymakers about integrating fitness assessments into school curricula, fostering a culture of health and fitness among students. Addressing these aspects, the research contributes to the broader goal of promoting a healthier lifestyle and improving athletic outcomes in school sports programs